Osteoblast‐Derived Giant Plasma Membrane Vesicles Induce Osteogenic Differentiation of Human Mesenchymal Stem Cells. Issue 9 (25th July 2018) - Gaur, Deepanjali; Yogalakshmi, Yamini; Kulanthaivel, Senthilguru; Agarwal, Tarun; Mukherjee, Devdeep; Prince, Ashutosh; Tiwari, Anuj; Maiti, Tapas K.; Pal, Kunal; Giri, Supratim; Saleem, Mohammed; Banerjee, Indranil
Abstract: Exosome‐mediated differentiation of human mesenchymal stem cell (hMSC) has opened up a new possibility for the directed osteogenic differentiation of hMSC by the osteoblast‐derived vesicles. Here, it is hypothesized that giant plasma membrane vesicles (GPMVs) generated from osteoblast, can direct the osteogenic differentiation of hMSC. GPMVs having different membrane characteristics are generated from osteoblast cells (MG‐63) using chemical vesiculants. It is deciphered that there is a treatment‐dependent variation in the size and complexity in the GPMVs. It is also showed a variation in lipid composition among the GPMVs. It is demonstrated that GPMVs can be fused with hMSC in vitro and such fusion has no detrimental effect on the viability of hMSC. Further, it is showed that there is a significant increase in the expression of osteogenic differentiation markers in GPMV‐fused hMSC at protein and mRNA level. A close correlation between the extent of fusion and the degree of osteogenic differentiation is observed. The GPMV reported here may be explored for future application in bone tissue engineering. Abstract : Giant plasma membrane vesicles (GPMVs) of different membrane characteristics are produced from the osteoblast cells using chemical vesiculants and are characterized in terms of size, yield, lipid composition, and structural complexity. GPMVs are fused with human mesenchymal stem cell in vitro. The GPMV‐fused hMSC are found viable and underwent osteogenic differentiation in vitro.